An Analysis of Hadiths on the Virtues of Seeking Knowledge from the Perspective of Contemporary Islamic Education - Citra Anisatun Nabila; Amelia Risma Sufrotin Nida; Erfan Soebahar; Kasan Bisri (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: This study aims to examine the quality and meaning of hadiths regarding the virtues of seeking knowledge; the educational values contained in these hadiths; and the relevance of these hadiths to contemporary Islamic education. Methodology: This study employs a qualitative approach in the form of a literature review. Data collection in this study was conducted using the documentation technique, which involves reviewing and identifying various sources relevant to the research focus. Data analysis uses the content analysis method, which involves several stages: data collection, data reduction, data presentation, and conclusion. Main Findings: Research shows that this hadith is authentic and embodies spiritual values, motivation to learn, character building, and social responsibility. This hadith is relevant to contemporary challenges such as fostering a culture of lifelong learning, strengthening students’ character, increasing motivation, and using technology positively. Thus, this hadith can serve as a conceptual foundation for developing an adaptive Islamic education that does not neglect its spiritual and moral dimensions. Novelty/Originality of this study: This hadith can serve as a conceptual foundation for the development of Islamic education that adapts to the changing times without losing its spiritual and moral dimensions.